The conditions for effective agricultural development assistance in the Ivorian context: Les conditions d’une efficacité de l’aide agricole au développement dans le contexte Ivoirien (International Journal of Scientific Research and Management (IJSRM), 2022)
This article focuses on the conditions for the effectiveness of development aid for the Ivorian agricultural sector. Speaking of development aid, this study focuses on official development assistance for agriculture, better known as agricultural ODA. The study was conducted in both the Abidjan (south) and Korhogo (north) areas. Following a qualitative tradition conducted using purposive sampling and snowballing techniques, we conducted a total of eighteen (18) interviews with approximately twenty-five (25) respondents as part of this research. Three (3) categories of actors were targeted : institutional or structural actors at the national level (AISN), local structural actors (ASL) and peasant actors (AP). The study revealed that the constraints that obstruct the effectiveness of agricultural ODA in the Ivorian context are "political-economic", "structural-institutional" and "practical-rural".